Application of Plant Defense Elicitors Fails to Enhance Herbivore Resistance or Mitigate Phytoplasma Infection in Cranberries - Rodriguez-Saona, Cesar; Polashock, James J.; Kyryczenko-Roth, Vera; Holdcraft, Robert; Jimenez-Gonzalez, Giovanna; De Moraes, Consuelo M.; Mescher, Mark C. (Frontiers in Plant Science, 2021)
Synthetic elicitors of the salicylic acid (SA) and jasmonic acid (JA) plant defense pathways can be used to increase crop protection against herbivores and pathogens. In this study, we tested the hypothesis that elicitors of plant defenses interact with pathogen infection to influence crop resistance against vector and nonvector herbivores. To do so, we employed a trophic system comprising of cranberries (Vaccinium macrocarpon), the phytoplasma that causes false blossom disease, and two herbivores—the blunt-nosed leafhopper (Limotettix vaccinii), the vector of false blossom disease, and the nonvector gypsy moth (Lymantria dispar). We tested four commercial elicitors, including three that activate mainly SA-related plant defenses (Actigard, LifeGard, and Regalia) and one activator of JA-related defenses (Blush). A greenhouse experiment in which phytoplasma-infected and uninfected plants received repeated exposure to elicitors revealed that both phytoplasma infection and elicitor treatment individually improved L. vaccinii and L. dispar mass compared to uninfected, untreated controls; however, SA-based elicitor treatments reduced L. vaccinii mass on infected plants. Regalia also improved L. vaccinii survival. Phytoplasma infection reduced plant size and mass, increased levels of nitrogen (N) and SA, and lowered carbon/nitrogen (C/N) ratios compared to uninfected plants, irrespective of elicitor treatment. Although none of our elicitor treatments influenced transcript levels of a phytoplasma-specific marker gene, all of them increased N and reduced C/N levels; the three SA activators also reduced JA levels. Taken together, our findings reveal positive effects of both phytoplasma infection and elicitor treatment on the performance of L. vaccinii and L. dispar in cranberries, likely via enhancement of plant nutrition and changes in phytohormone profiles, specifically increases in SA levels and corresponding decreases in levels of JA. Thus, we found no evidence that the tested elicitors of plant defenses increase resistance to insect herbivores or reduce disease incidence in cranberries.